Objects of Crime: Bodies, Embodiment and Forensic Pathology. (October 2020) - Jones, Imogen
When a death takes place in suspicious circumstances, the body transitions from being somebody to an object which is of legal as well as social value. A key investigatory process is that of the forensic autopsy, carried out by a Home Office Registered Forensic Pathologist (HORFP). This article draws upon empirical data from research involving HORFPs to examine their identity and the meaning they assign to the deceased body. I argue that HORFP's understanding of the value of the deceased body constantly shifts due to the multifaceted nature of their role. I explain this by drawing upon a legal embodiment framework. The HORFPs have to balance a legal context which demands objective 'facts' and formal labels with emotionally difficult cases and the impact of their work on the bereaved. I challenge the dichotomy between dualism and embodiment, arguing that there is not an oppositional choice between 'science' and recognition of the symbolic value of the corpse, but rather that these views can coexist while serving different functions that are central to a HORFP's role.